2022
DOI: 10.1017/s1368980022002592
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in energy drink consumption among UK adolescents: a mixed-methods study

Abstract: Objective: To examine energy drink consumption among adolescents in the United Kingdom (UK) and associations with deprivation and dietary inequalities. Design: Quantitative dietary and demographic data from the National Diet and Nutrition Survey (NDNS) repeated cross-sectional survey were analysed using logistic regression models. Qualitative data from semi-structured interviews were analysed using inductive thematic analysis. Setting: UK Participants: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…This example demonstrates the need for government policy to be effectively implemented and enforced across different types of food outlets. As previous research has shown energy drink consumption is increasing among adolescents from deprived backgrounds ( Vogel et al , 2022 ), mandatory restrictions on the sale of energy drinks have the potential to help address dietary inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…This example demonstrates the need for government policy to be effectively implemented and enforced across different types of food outlets. As previous research has shown energy drink consumption is increasing among adolescents from deprived backgrounds ( Vogel et al , 2022 ), mandatory restrictions on the sale of energy drinks have the potential to help address dietary inequalities.…”
Section: Discussionmentioning
confidence: 99%